Principles of organizational structuring of management of socio-economic system - Устенко, А. О.; Малинка, О. Я. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The peculiarities of organizational structuring of managing socio-economic system (SES) are considered. The approach is based on the conceptual model which consists of system ideas about the conditions (external and internal) – Х – У; objectives and processes of their achievement in the competitive environment – X; resources for achieving the objectives – У; management – Z. The following systemic aspects are researched: 1) the purpose and the actual process as an elementary transformation; 2) personal and material factors which are involved in the "transformation" of resources into labor products; 3) the "transformation" technology (logistics); 4) belonging to the stage of economic activity (or a set of stages); 5) belonging to a certain subsystem of management system; 6) belonging to management link (of a certain level); 7) management system in the process of creating labor products in general. The peculiarities of managing labor process model are considered, as labor of the professionals in management field, at all levels and links of the organizational structure of management object, labor of the personnel who directly implements management process, labor of the personnel of automated management systems exploitation, if management is performed with appropriate methods and means, using advanced information systems. The role of information in management process is described.